Jewish Theology, Systematically and Historically Considered - Kohler, Kaufmann, 1843-1926 (Salt Lake City, UT : Project Gutenberg, 2010)
"Jewish Theology, Systematically and Historically Considered" by Kaufmann Kohler is a systematic theological work written in the early 20th century. This scholarly publication explores the Jewish faith with a focus on its doctrines, historical development, and its unique characteristics compared to other religions, particularly Christianity and Islam. It delves into the essential beliefs, the concept of God, and the moral and spiritual implications of Judaism, aiming to present a cohesive understanding of Jewish theology. The beginning of the text sets the stage for an in-depth exploration of Judaism as both a religious and ethical system, emphasizing its historical growth and the dynamic nature of its beliefs. Kohler discusses the meaning of theology, contrasting it with philosophy and establishing a framework for understanding Jewish spirituality. He articulates the necessity of this work amid a landscape where systematic expounding on Jewish faith had been largely absent, aiming to clarify Judaism's essential truths and its relationship with broader human experiences. This early section lays a profound foundation for understanding the evolving nature of Jewish thought as a living tradition, rather than a rigid set of dogmas. (This is an automatically generated summary.)
Release date is 2010-06-06
Keywords: Judaism -- Doctrines